Sistem Informasi Inventaris Sarana Dan Prasarana Sekolah Berbasis Web Dengan Metode Sistem Development Life Cycle (SDLC) - Firmansyah Firman; Adie Kusna Wibowo; Amat Damuri (STMIK Al Muslim, 2026)
The management of facilities and infrastructure inventory at SMP Al Muslim previously faced challenges regarding efficiency, accuracy, and data transparency... This research aims to design and implement a structured and computerized web-based inventory information system. The development method used is the System Development Life Cycle (SDLC)... The result is a Web-Based Inventory Information System that is effective in enhancing the transparency, accuracy, and efficiency of school facilities and infrastructure management.